Method Development and Validation of Sulphadiazine in Bulk and Pharmaceutical Dosage Form by UV-Spectrophotometric Method - Vandana, Kothakota (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT: A new, simple, precise and accurate method for the estimation of Sulphadiazine in bulk and pharmaceutical dosage form has been developed. A mixture of methanol and water (90:10) was chosen as the solvent system. The ?Ä??max was found to be 270nm. The responses were linear in the range of 05-30?é?Ág/ml. The regression equation of the calibration graph and correlation coefficient were found to be y = 0.099x + 0.031 and 0.999 respectively. Validation of the method was done in order to demonstrate accuracy, precision, interday and intraday assay, robustness and ruggedness of the proposed method. The %RSD values for both intraday and interday precision were less than 1%. The recovery of the drug from the sample was ranged between 99.48% and 100.90%. Commercial tablets containing 500mg of Sulphadiazine (SULPHADIAZINE manufactured by Abbot Healthcare Pvt. Ltd. Mumbai) were analyzed by the proposed method and the results were well within the claimed limits.